(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the incidence and management outcome in female patients who come to general surgeon with acute abdomen due to certain gynecological reason. Study Design: Descriptive / randomized study Place and Duration of Study: This study was conducted at the Emergency Department, K.M.C/Civil Hospital Khairpur (Mir’s) from 1st August 2014 to 30 May 2016. Materials and Methods: All those female cases were included in this study, who went through the process of exploratory laparotomywith accidental finding of underlying gynecological pathology. All described cases were documented in specific proforma, tabulated and statically classified and the final results were prepared. Results: Over the period of two years, 314 female patients were received in A/E department of this hospital with acute abdomen and were managed. Among these 53 (17%) were those patients, where the cause of acute abdomen was certain gynecological pathology. The mean age was 37 years and most of them were married, 42 (79.24%) and multiparous, 35 (66%). Pain in Right lower quadrant was the commonest symptoms, pelvic inflammatory disease 13 (24.53%) was major cause, followed by ovarian torsion 10 (18.86%) and ruptured ovarian cyst 9 (17%). Clinical diagnosis and Ultrasonography were little helpful to reach at correct diagnosis in present series of cases. Here the reason of exploration was due to the clinical findings of appendicitis, it’s complications or peritonitis. Conclusion: Acute abdomen in females, requires full clinical, laboratory and radiological evaluation. If such situation arises where gynecological pathology is encountered after exploration, then the gynecological help and advice should be taken before doing any procedure.